2005
DOI: 10.1038/sj.emboj.7600785
|View full text |Cite
|
Sign up to set email alerts
|

Boat, an AXH domain protein, suppresses the cytotoxicity of mutant ataxin-1

Abstract: Ataxin-1 is a neurodegenerative disorder protein whose glutamine-repeat expanded form causes spinocerebellar ataxia type 1 (SCA1) in humans and exerts cytotoxicity in Drosophila and mouse. We report here that the cytotoxicity caused by ataxin-1 is modulated by association with a related protein, Brother of ataxin-1 (Boat). Boat and ataxin-1 share a conserved AXH (ataxin-1 and HMG-box protein 1) domain, which is essential for both proteins' interactions with the transcriptional corepressor SMRT and its Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 31 publications
5
93
0
Order By: Relevance
“…It was also shown that if the proteasome was pharmacologically inhibited, there was an increase in ubiquitylated Sens/Gfi-1, suggesting that ataxin-1 enhanced the degradation of Sens/Gfi-1 via the ubiquitin proteasome system. This is interesting in light of the second report in which the level of Boat (Brother of ataxin-1) was reduced in the Purkinje cells of SCA1 transgenic mice (Mizutani et al 2005). It was not demonstrated that this was due to enhanced proteasomal degradation, but it seems probable in light of the Sens/Gfi-1 result.…”
Section: Sca1: Corepressors and Remodeling At Sites Of Transcriptionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was also shown that if the proteasome was pharmacologically inhibited, there was an increase in ubiquitylated Sens/Gfi-1, suggesting that ataxin-1 enhanced the degradation of Sens/Gfi-1 via the ubiquitin proteasome system. This is interesting in light of the second report in which the level of Boat (Brother of ataxin-1) was reduced in the Purkinje cells of SCA1 transgenic mice (Mizutani et al 2005). It was not demonstrated that this was due to enhanced proteasomal degradation, but it seems probable in light of the Sens/Gfi-1 result.…”
Section: Sca1: Corepressors and Remodeling At Sites Of Transcriptionmentioning
confidence: 95%
“…The roles of regions outside the polyglutamine stretch in mediating mutant ataxin-1 toxicity have been established; however, two recent reports have underscored the importance of ataxin-1's AXH (ataxin-1 and HMGbox protein 1) domain in mediating transcriptional regulatory events and neurodegeneration (Mizutani et al 2005;Tsuda et al 2005). Overexpression of mutant ataxin-1 resulted in a reduction of the transcription factor Senseless (Sens)/Gfi-1 in Purkinje cells.…”
Section: Sca1: Corepressors and Remodeling At Sites Of Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A self-association region of the non-expanded protein was mapped in the centre of the protein and identified to overlap the only certified globular domain of the otherwise PeerJ PrePrints | http://dx.doi.org/10.7287/peerj.preprints.259v1 | CC-BY 4.0 Open Access | received: , published: 27 Feb 2014 mostly unstructured protein, the AXH domain that spans residues 562-689 (SMART SM00536) (Burright et al, 1997;de Chiara et al, 2003). This motif is functionally very important as it is involved in transcriptional regulation as well as in the RNA-binding activity of ataxin-1 (Matilla et al, 1997;Okazawa et al 2002;Tsai et al, 2004;de Chiara et al, 2003;de Chiara et al, 2005;Mizutani et al, 2005;Tsuda et al 2005;Lam et al, 2006;Serra et al, 2006;Goold et al, 2007;Lee et al 2011). AXH is also necessary and sufficient for the majority of the known interactions of ataxin-1 with other proteins, most of which are transcriptional regulators (Tsai et al, 2004;Tsuda et al 2005;Lam et al, 2006;Goold et al, 2007;Serra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Second to RNA binding, the AXH domain contains a cluster of charged surface residues that allows for another secondary binding surface. This leads to the several protein-protein interactions through the ataxin-1 AXH domain, namely a paralog of ataxin-1, brother of ataxin-1 (BOAT), which also contains a AXH domain, the SMRT/SMRTER and Capicua proteins [94]. These interactions, along with interactions between several transcriptional factors, give ataxin-1 its transcriptional repression activity [90,91,93].…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%